(untitled) (Comillas Journal of International Relations, 2018)
The article presents the findings of a research on the EU response to the crisis caused by the growth of the inflow of irregular migrants in Europe in 2011 and the following years. The first section examines the causes of the current migration flows in general terms and explains why many European citizens and political leaders are hostile to the arrival of migrants most of whom are forced to leave their home. In the second section, the management of the migration crisis by the EU leaders is analysed with the concepts and tools of the TransCrises project, an H2020 research about managing trans-boundary risks and crises. In particular, this section reviews how the EU leaders have operated the seven management tasks that experts deem as important to bring a crisis to not harmful consequences. In the concluding section, the EU management of the migration crisis is assessed and advices are given for upgrading the management.